Three decades of monitoring the responses to alkaline K-rich applications in an acidified, K-deficient Norway spruce (Picea abies) stand reveals that forest restoration depends on treatment type: Rock dust, wood ash, dolomite and/or potassium sulphate - Van Der Bauwhede, Robrecht; Schillebeeks, Nele; Hartmann, Peter; von Wilpert, Klaus; Habel, Raphael; Vancampenhout, Karen; Smolders, Erik; Muys, Bart (Geoderma, 2025)
[Display omitted] •Long-term effects of amendments on K-deficient Norway spruce stand (28 years)•Base cation loss coupled with nitrate and DOC leaching.•Soil organic carbon increased with K2SO4, decreased with phonolite rock dust.•Tree growth correlates with available K applied.•Ellenberg N increase due to amendments. Wood ash and rock dust have been suggested as suitable soil amendments to restore acidified and nutrient-depleted forests, but long-term data are generally lacking to justify the claims. The biogeochemical responses to such amendments were monitored during 28 years post applications in a potassium (K)-deficient Picea abies L. stand on acidified loam (topsoil pH-CaCl2 = 3.2) in Ochsenhausen (Germany). The five amendments included wood ash (10 Mg/ha) and the rock dust phonolite (10 Mg/ha), both referenced to dolomite (10 Mg/ha), K2SO4 (1 Mg/ha), or the combination of both (1 Mg K2SO4/ha + 6 Mg dolomite/ha). Radial tree growth did not respond to dolomite or rock dust but responded to wood ash and responded most strongly to all mineral K treatments, i.e., growth (R2 = 0.83) and foliar K concentrations could be predicted by the applied available K in the treatment. The K-feldspar in the rock dust dissolved too slowly to supply sufficient K. Calcium loss from 80 cm depth was highest in the wood ash treatment and was mainly accompanied by nitrate leaching (up to 35 kg N/ha/yr), but it was more moderate with the K2SO4 + dolomite mixture (humus solution pH 5). The K2SO4 treatment increased ecosystem carbon (C) sequestration (including tree biomass and 0–40 cm mineral soil) with 1.3 Mg C/ha/year above the unamended control. The community weighted mean Ecological Indicator Values (EIVE) for fertility (N) slightly increased in the herb layer for the plots that received alkaline amendments. The amendments also increased the diversity indices of the herb layer without the loss of calcifuge species. It is concluded that the phonolite rock dust did not restore forest vitality and that most positive effects are obtained with K fertilisation. The combination of K2SO4 + dolomite also stimulated tree growth and carbon stocks in the organomineral soil, but the liming effect also decreased the forest floor C-stock, leading to counteracting effects on the C-balance.